Effects of polishing treatments on the interface between garnet solid electrolyte and lithium metal. (10th February 2023) - Ma, Xiaoning; Xu, Youlong
Highlights: In-depth study of the polish treatment of garnet-type solid electrolyte surface. The more contact sites between the electrolyte and lithium metal are necessary to be provided. The interfacial resistance between garnet polished by 600 grit abrasive paper and Li is reduced to 20.9 Ω cm 2 . Abstract: Garnet Li7 La3 Zr2 O12 (LLZO) is an attractive and highly promising solid electrolyte, has made a significant progress in the battery performance to achieve higher energy density and better safety. However, the poor wettability between the interface of garnet and Li metal anode leads to high interfacial impedance and the penetration of Li dendrites during cycling, which limits the practical application of garnet. Polishing treatment is a very simple and convenient physical treatment method for the surface of garnet. Here, we investigate the effects of surface treatment of Li6.25 Al0.2 La3 Zr2 O11.85 Br0.15 (LALZOBr0.15 ) with different grit sizes of sandpaper on the wettability and interfacial resistance between it and Li metal. Compared to coarse and very fine sandpaper, the LALZOBr0.15 –600 electrolyte polished with 600-grit sandpaper was significantly reduced the interfacial impedance to 20.9 Ω cm 2, ensuring tight contact at the Li|LALZOBr0.15 –600 interface, thereby further inhibiting the growth of Li dendrites. Moreover, benefiting from the excellent interface, Li|LALZOBr0.15 –600|Li symmetric cell exhibited an excellent cycling stability and could be cycled at 0.3 mA cm −2 over 1300 cycles without short-circuiting. Applying it to quasi-solid-state batteries and all-solid-state batteries, which also showed great electrochemical performance. Our work demonstrates the importance of using a moderate grit sandpaper for electrolyte surface treatment. Graphical abstract: Image, graphical abstract